Rancang Bangun Media Pembelajaran Puasa Bagi Anak Menggunakan Pendekatan Multimedia Development Life Cycle Berbasis Android - Diki Arisandi; Salamun Salamun; Wahyu Hermawan (STMIK Budi Darma, 2022)
Children need to obtain information regarding the fasting ritual from the fun references because fasting is compulsory, and listed in the pillars of Islam, as well as several letters in the Al-Qu'ran. Fasting educational media for children aim to provide information about fasting and help Muslims, especially children aged 5-11 years, in understanding the fasting ritual. An electronic-based learning medium of Fasting built based on the Android platform and using the multimedia development life cycle approach, a method or approach in building multimedia applications which are combining images, sound, video, animation, and others. The learning medium will be tested using alpha testing before being tested on the user. The testing is continued by involving a group of children using pre-test and post-test, to get an overview of knowledge regarding fasting before and after using the application. The average pre-test result was 50.83%, while in the post-test the average result increased by 90.29%. Based on the results mentioned before, shows that this Android-based fasting education learning medium for children is can be used as a learning media